Collocations with Adjective ‘Bleu’ in French: A Study Based on Lexicographic and Corpus Data - Yu. V. Bogoyavlenskaya; D. A. Paliychuk (Научный диалог, 2025)
This article investigates the collocational patterns of the adjective ‘bleu’ as found in lexicographic sources and a representative corpus of French texts. The data for this analysis were extracted from nine traditional and electronic French dictionaries, as well as from the frTenTen 2023 corpus hosted on the Sketch Engine platform. The findings reveal significant discrepancies in the quantity and nature of the syntagmatic partners of ‘bleu’ between lexicographic sources, with their annotations not aligning. A lexical index was employed to rank dictionary collocations from the most frequently represented to the rarest, reflecting the proportion of dictionaries that include the keyword ‘bleu’. The analysis of automatically extracted collocations from the corpus refuted the hypothesis of a positive correlation between dictionary and corpus indicators. Approximately 70% of dictionary combinations do not appear in the list of the most frequent collocations within the mega-corpus. It is demonstrated that corpus-based collocations more accurately reflect the political, economic, technical, and sociocultural realities of contemporary society, whereas dictionary entries illustrate usage in specialized fields (medical, botanical, zoological, geological). Furthermore, it has been established that the adjective ‘bleu’ is frequently used in figurative meanings not documented in lexicographic sources.